Problemy stosunku między funduszami własnymi przedsiębiorstw a kredytami bankowymi przy finansowaniu materialnych środków obrotowych - Vogel, Heinz (Wydział Prawa i Administracji UAM, 1976)
The aim of the paper is to answer the following question: what are the socially indispensables relations between own fund of enterprises and bank credits. The author examines two main problems: a) the interpretation of the relation between the total amounts of own financial resources of enterprises and indispensables bank credits, b) the way of allocation of total own funds in national economy among the particular branches of the economy and enterprises.
The Relation between Own Funds of Enterpreises and Bank Credits in Financing the Working Assets in Operation